Характеристика електрофоретичних спектрiв естераз насiння Saussurea discolor (Willd.) DC. та S. porcii Degen. - Марченко, М.М.; Шелифiст, А.Є.; Чебан, Л.М. (Видавничий дім "Академперіодика" НАН України, 2008)
We investigated the electrophoretic spectrum of esterase of seeds S. discolor and S. porcii. The isoenzyme spectrum of esterase of seeds of the explored species is shown to be characterized by a high number of the components with the low electrophretic mobility. Particularly, this is expressed for the alkaline forms of the enzyme.